Methylation-specific, universal, and highly sensitive identification of ctDNA in prostate cancer by multiplex droplet digital PCR - Søren Kahns; Ahmed H. Zedan; Mads M. Aagaard; Luisa M. D. Canto; Sanne Kjær-Frifeldt; Stine V. Eriksen; Christine V. Madsen; Jonna S. Madsen; Palle J. S. Osther; Torben F. Hansen; Rikke F. Andersen (PLoS ONE, 2026)
Objective Liquid biopsy for detection of circulating tumor DNA (ctDNA) offers a promising, non-invasive strategy for real-time monitoring of cancer. We aimed to develop a universal and sensitive one-tube droplet digital PCR (ddPCR) multiplex assay able to detect ctDNA in plasma from metastatic prostate cancer (PCa) patients. Methods Publicly available array data are applied to identify methylation signatures specific to both normal and cancerous prostate tissue. The assay is based on the highly sensitive ddPCR technology, and tissue and plasma samples are analyzed using the QX600 ddPCR multiplexing platform from BioRad. Results We identified three novel genomic regions, ACTRT2 , EVX1, and HOXD13 , containing CpG-methylation signatures specific to normal and cancerous prostate tissue. We successfully targeted the three biomarkers in a single-tube methylation-specific multiplex ddPCR (mm-ddPCR) assay along with two previously reported PCa-specific hypermethylated CpG biomarkers, DOCK2 and HAPLN3 , and the ALB reference gene. The mm-ddPCR assay consistently detected ACTRT2 , EVX1, and HOXD13 across all samples originating from prostate-derived tissue. In contrast, the HAPLN3 and DOCK2 biomarkers were predominantly detected in PCa tissue. We also demonstrate that the five ctDNA biomarkers can be detected in plasma samples from metastatic castration-resistant PCa (mCRPC) patients with a 95% CI (85%, 100%) using the mm-ddPCR assay. Conclusion This work demonstrates that the mm-ddPCR assay offers a simple, fast, cost-effective, sensitive, and universal tool for the detection of ctDNA biomarkers in plasma from mCRPC patients. Further studies are required to explore its potential for PCa risk stratification and treatment guidance.